Is signal resolution of linear cryocatheters appropriate to map superoparaseptal accessory pathways? A comparison with Orion high‐resolution mapping. Issue 5 (2nd August 2020) - Ducceschi, Valentino; Maddaluno, Francesco; Del Giorno, Giuseppe; Catalano, Angelo; Carbone, Angelo
Abstract : Larger tip cryoablation catheters can dampen the signal at the distal tip reducing the resolution of mapping of supero paraseptal APs. The aid of high resolution mapping should be considered to improve safety and efficacy.